Attitudes of high school students in Samtah Governorate towards the use of electronic exams through the Future Gate in light of the (COVID-19) Corona pandemic - AL- Ibrahim, Mohamed Naser; Mubaraki, Fawzia Hamad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to reveal the trends of high school students in Samtah Governorate towards the use of electronic exams through the portal of the future in light of the Corona pandemic (COVID-19). The study used the descriptive and analytical approach, the study sample consisted of (341) female students from Al-Marjila secondary school, to whom a questionnaire consisting of a vertebra was applied, divided into four axes. The results of the study showed that the students ’attitudes towards using electronic tests through the Future Gate were high, with an arithmetic average (3.52) and a relative weight (70%). The first rank was the axis of development achieved by the use of electronic tests through the Future Gate with an arithmetic average (3.64) and a relative weight (72.8%), while the axis of the benefits of using electronic tests through the Future Gate came in the second order with an arithmetic average (3.53) and a relative weight. (70.6%), followed by the axis of desire The use of electronic tests through the future portal is in the third order with an arithmetic average (3.51) and a relative weight (70.3%), while the fourth and final axis of obstacles to the use of electronic tests on the future portal came in the middle of arithmetic (3.4) and a relative weight (68%). Results: Any statistically significant differences in the attitudes of high school students in Samtah governorate towards the use of electronic tests through the future portal due to the academic grade variable. The study recommended the necessity of raising awareness among students and teachers of the importance of electronic tests, qualifying and training them to use them through the various available devices, and spreading the culture of electronic tests among students, teachers and the local community. And conducting comparative studies on electronic tests in different environments.